Autarkic desorption electrospray ionization source for on-site analysis of consumer goods. Issue 16 (6th July 2020) - Lotz, Florian; Gerbig, Stefanie; Lotze, Christian; Spengler, Bernhard; Schulz, Sabine
Abstract : A battery-powered DESI source with integrated solvent/gas supply and novel sampling geometry is presented for daily-goods analysis. Abstract : A general-purpose desorption electrospray ionization (DESI) source is presented which is not bound to the laboratory site. It allows autarkic operation for a few hours and can be connected to different types of (autarkic or non-autarkic) mass spectrometers via an atmospheric-pressure interface. Technical characteristics are described as well as results from direct surface analysis of consumer goods such as plastics, fruit peels or pills, or from living objects such as human skin, demonstrating the detection of various target compounds such as plasticizers, pesticides, drugs or sun blockers. Quantitative analysis is demonstrated for phthalates in plastics. The geometry of the sample, the sample table and the sprayer were modified and characterized for optimization of the method. The autarkic ion source has a total size of 48.4 × 27.0 × 18.0 cm ( l × w × h ) and a total mass of 7 kg. The source delivers 5.5 bar pressurized air and an adjustable solvent flow rate down to 1.5 μl min −1 for the DESI sprayer. A rechargeable 25.6 V battery allows autarkic runtimes of more than 3.5 hours. Source optimization and characterization was done on an orbital trapping mass spectrometer. Connected to a portable mass spectrometer, the developed device makes DESI suitable for on-site analyses in e.g. consumer protection, border control or homeland security.